PERANCANGAN GALERI BARONGSAI INTERAKTIF DI KOTA DENPASAR (Jurnal iSpectrum, 2023)
Lion dance is a traditional acrobatic dance performance originating from China. The Lion dance is performed by two individuals wearing costumes resembling lions, accompanied by musical instruments. This performance is often held during Chinese New Year celebrations, weddings, and business openings, as it is believed to bring good luck. Lion dance has a rich history and cultural significance, gaining popularity worldwide, including in Indonesia. In Indonesia, lion dance is part of the Intangible Cultural Heritage and has its own dedicated organization, known as FOBI. The development of lion dance in Indonesia has experienced ups and downs due to politics and the COVID-19 pandemic. To preserve and protect the unique cultural heritage of lion dance from fading away over time and to pass it on to future generations, facilities are needed to support this art form. A Lion Dance Gallery can be an alternative to safeguard and preserve the lion dance culture, integrating a Contemporary Chinese theme with a Balance-Harmony concept. This approach combines traditional materials and motifs with modern elements, creating a design that incorporates Feng Shui principles to emphasize balance and harmony. The gallery serves as a means to uphold and transmit the essence of lion dance culture to generations to come.